Photoalignment of Liquid Crystals on Chalcogenide Glass As20Se80 Surface - Boyarchuk, N.; Kurioz, Yu.; Slyusarenko, K.; Trunov, M.; Reznikov, Yu. (Ukrainian Journal of Physics, 2012)
Photoalignment of nematic liquid crystals on the chalcogenide glass As20Se80 surface is studied by the digital processing of the optical textures of light-induced twist deformations of a liquid crystal (LC) in a cell irradiated with Gaussian polarized light. The original experimental method allowed obtaining the dependence of the light-induced twist angle for the As20Se80 surface on the exposure dose by the analysis of the only irradiated spot. The dependences of the light-induced twist angle on the exposure dose are found to be qualitatively different for LC 5CB and LC E7, which points on a possibility of different mechanisms of photoalignment on chalcogenide glass.